Non‐Porous versus Mesoporous Siliceous Materials for CO2 Capture. Issue 6 (27th May 2019) - Vittoni, Chiara; Gatti, Giorgio; Paul, Geo; Mangano, Enzo; Brandani, Stefano; Bisio, Chiara; Marchese, Leonardo
Abstract: In this study, the adsorption properties of a Stöber silica‐based material towards CO2 were evaluated for the first time. The use of Stöber silica as support is interesting for real technological applications mainly due to economic factors. Furthermore, a direct comparison between the non porous Stöber sample with an ordered porous material (based on MCM‐41 silica) allowed to evaluate the effect of the porosity on the CO2 adsorption properties. In order to make silica materials reactive towards CO2, they were functionalized by introducing amino groups via grafting of 3‐[2‐(2‐aminoethyl)aminoethyl]aminopropyltrimethoxysilane. After a qualitative study of the CO2 adsorption, the quantitative determination of CO2 adsorption capacity at 35 °C revealed that the mesoporous material is more efficient compared to the Stöber‐based one (adsorption capacity values of 0.49 and 0.58 mol/kg for Stöber‐based and mesoporous samples). However, since the difference in the adsorption capacity is only about 15 % and the Stöber‐based sample is considerably cheaper, the non‐porous sample should be considered as a favourable adsorbent material for CO2 capture applications. Abstract : Finding the right porosity : The CO2 adsorption properties of a cheap Stöber‐based adsorber have been investigated and compared with those of a MCM‐41‐based material, traditionally used for CO2 capture applications.